TREM2 is associated with the risk of Alzheimer's disease in Spanish population - Benitez, Bruno A.; Cooper, Breanna; Pastor, Pau; Jin, Sheng-Chih; Lorenzo, Elena; Cervantes, Sebastian; Cruchaga, Carlos (Neurobiology of aging, 2013)
Two recent studies have reported the association of rs75932628-T in the TREM2 gene with the risk for Alzheimer's disease (AD). Rs75932628-T is a rare nonsynonymous variant (p.R47H) that confers a high risk of AD with an effect size similar to that of the APOE ɛ4 allele. However, this association has not been replicated in any independent studies to date. The allelic frequency of rs75932628 varies according to the population from 0.02% to 0.63% among healthy controls. In an attempt to replicate the association between rs75932628-T and AD risk, we genotyped rs75932628 in a cohort of 504 AD subjects and 550 healthy controls from a Spanish population. Rs75932628-T showed a minor allele frequency of 0.3% among this cohort. Interestingly, in our study, rs75932628-T was found exclusively in 1.4% of AD cases (7/504), including 4 early-onset AD cases, and in none of the controls (n = 0/550). Here, we report the first positive replication study in a Spanish population and confirm that TREM2 rs75932628-T is associated with the risk for AD.